Freeze‐dry processing of three‐dimensional cell constructs for bone graft materials. Issue 3 (26th July 2019) - Sasaki, Jun‐Ichi; Yoshimoto, Itsumi; Katata, Chihiro; Tsuboi, Ririko; Imazato, Satoshi
Abstract: Freeze‐dry processing improves the operability and stability of cell‐based biomaterials and facilitates sterilization for clinical application. However, there is no established freeze‐drying protocol for engineered tissues. Recently, we reported that biomimetic bone tissues can be fabricated using scaffold‐free three‐dimensional (3D) cell constructs with potential applications as bone graft materials. The purpose of this study was to assess the influence of freeze drying on the morphology and components of 3D cell constructs. Cell constructs freeze dried in phosphate buffered saline (PBS) maintained organic and inorganic components; whereas sodium citrate buffer (SCB)‐treated constructs had significantly lower amounts of calcium and bone‐related proteins. Alkaline phosphatase (ALP) activity in cell constructs was maintained by freeze drying in 10% sucrose‐containing PBS, whereas cell constructs treated with PBS without sucrose or with sucrose‐containing SCB showed significant reductions of ALP activity. In this study, we found that sucrose‐containing phosphate buffer was suitable for freeze drying to maintain minerals and protein functions within 3D cell constructs, whereas citrate buffer was inappropriate. The insights gained by this study may facilitate the development of novel cell‐based biomaterials fabricated by tissue engineering approaches and bone graft biomaterials.